Pelatihan Penggunaan Aplikasi SIAPIK Bank Indonesia Kepada Pelaku UMKM Desa Krikilan - Dewi Ismoyowati; Vicky Pratama Mahardika; Fahrul Ramadhan; Dewi Reina Sari; Dzakiya Salma Rahmatika; Dian Alvina Purwisanti; Muhammad Rizal Musyafa; Nabillah Azzahrah; Nafil Farhan Fauzi; Novallino Setyanto Nugroho; Putri Shafira; Dovanka Casachi (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
This community service aims to improve the financial literacy of MSMEs in Krikilan Village, Kalijambe District, Sragen Regency through training in the use of the SIAPIK application from Bank Indonesia. SIAPIK, or the Financial Information Recording Application System, is designed to make it easier for MSMEs to record financial transactions and prepare financial reports in accordance with MSME Financial Accounting Standards. Participants in this activity were MSMEs from Krikilan Village, Kalijambe District, Sragen Regency, totaling 20 people. This activity involved socialization and training using lecture, dialogical, and direct practice methods. The implementation of the training on July 18, 2024 showed positive results, with MSME participants now having a better understanding of the use of the SIAPIK application. This program is expected to improve the technical skills of MSMEs, facilitate access to financing, and improve the quality of their financial reports.